Analisis Faktor-Faktor Penurunan Angka Partisipasi Sekolah di Daerah Terpencil di Merauke - Kebubun, Rosina Jostina Marise (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the factors causing the decline in school participation rates (APS) in remote areas, focusing on Okaba District, Merauke Regency. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis, involving various education actors, including teachers, parents, community leaders, and local officials. The results of the study indicate that geographical factors such as poor road access, limited transportation facilities, and minimal education infrastructure are the main obstacles. In addition, community perceptions of formal education, family socio-economic conditions, and low community participation in the education process also worsen the situation. These findings emphasize the need for a contextual, participatory, and cross-sectoral policy approach to increase school participation in a sustainable manner. This study makes an important contribution to the design of education policies in border areas and disadvantaged areas in Indonesia.